Elucidating the potential of novel class biphenyl-phenyl acetate, IDD-AN-A1, an inhibitor targeting Isocitrate Lyase in Mycobacterium tuberculosis: a target to lead approach - Negi, Anjali; Perveen, Summaya; Kour, Harpreet; Sawant, Sanghapal D.; Sharma, Rashmi (Bioorganic Chemistry, 2026)
Isocitrate lyase (ICL), a pivotal enzyme of the glyoxylate shunt pathway in Mycobacterium tuberculosis (Mtb), represents an attractive target for the development of new anti-tuberculosis (TB) therapeutics. In this study, we identified 2-methoxy-4-((nitrosooxy)methyl)phenyl 2-(2-fluoro-[1,1 `-biphenyl]-4-yl)propanoate (IDDAN-A1) as a potent inhibitor of Mtb ICL. The compound exhibited strong activity against Mtb, with a minimum inhibitory concentration of 6.25 mu g/mL, and demonstrated potent inhibition in enzyme-based assays targeting ICL. Molecular docking studies further supported Mtb ICL as the potential molecular target of this compound. Cytotoxicity and hemolytic assays revealed a favorable safety profile for the compound with selectivity index >10. In combination studies, it exhibited additive and synergistic activity with the frontline drug Rifampicin and Delamanid respectively. Additionally, ex vivo assays simulating the intracellular environment of the pathogen demonstrated strong inhibitory potency. In vitro inhibition studies further confirmed the bacteriostatic nature of the compound across different concentrations. Collectively, these findings demonstrate that this molecule possesses promising anti-tuberculosis activity by targeting the ICL enzyme in Mtb.
Keywords: Anti-tuberculosis activity; Ex vivo; Isocitrate lyase; tuberculosis